Equalization of non-linear optical channels - Agarossi, L.; Bellini, S.; Bregoli, F.; Migliorati, P. (1998 IEEE International Conference on Communications, 1998)
This paper presents a comparative analysis of various linear and nonlinear equalizers for a high density optical channel. Since the read-out process is nonlinear, a suitable model based on the Volterra series has been adopted. We compare the performance and complexity of equalizers designed for linear and nonlinear channels. Specifically, the adaptive minimum mean square error (MSE), adaptive decision feedback equalizer (DFE), nonlinear adaptive Volterra equalizer (NAVE) and nonlinear adaptive decision feedback equalizer (NDFE) are analyzed, along with the maximum likelihood sequence estimator (MLSE), which is considered as a reference. Simulations show that the performance of classical structures (MSE, DFE, MLSE) is significantly reduced by the nonlinear response and that the NAVE and NDFE achieve a performance close to the MLSE, with lower complexity.